2017
DOI: 10.1371/journal.pone.0175351
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the severity of sleep apnea syndrome based on ballistocardiogram

Abstract: BackgroundSleep Apnea Syndrome (SAS) is a common sleep-related breathing disorder, which affects about 4-7% males and 2-4% females all around the world. Different approaches have been adopted to diagnose SAS and measure its severity, including the gold standard Polysomnography (PSG) in sleep study field as well as several alternative techniques such as single-channel ECG, pulse oximeter and so on. However, many shortcomings still limit their generalization in home environment. In this study, we aim to propose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…Afterwards, BCG signal is separated from the original composite pressure signal by performing drift compensation and digital filtering based on the built-in software, and eventually displayed on the PC. In [23], a real-time comparison between BCG signal collected by RS-611 and ECG signal collected by a commercial ECG collector (Prince 180D, ) was made, whose experimental results indicated that each wave trough of the collected BCG signal corresponded to a local minimum point of the collected ECG signal, which demonstrated the suitability of the collected BCG signal for analyzing and diagnosing cardiovascular diseases. In comparison with other wearable signal acquisition devices like ECG Holter [24], smart watch [25], smart chair [26], PPG based non-invasive blood pressure estimator [27] and cuff-based mercury sphygmomanometer, the MSM-based RS-611 is completely unobtrusive and the users do not need to attach any electrodes or devices on their body.…”
Section: Methodsmentioning
confidence: 99%
“…Afterwards, BCG signal is separated from the original composite pressure signal by performing drift compensation and digital filtering based on the built-in software, and eventually displayed on the PC. In [23], a real-time comparison between BCG signal collected by RS-611 and ECG signal collected by a commercial ECG collector (Prince 180D, ) was made, whose experimental results indicated that each wave trough of the collected BCG signal corresponded to a local minimum point of the collected ECG signal, which demonstrated the suitability of the collected BCG signal for analyzing and diagnosing cardiovascular diseases. In comparison with other wearable signal acquisition devices like ECG Holter [24], smart watch [25], smart chair [26], PPG based non-invasive blood pressure estimator [27] and cuff-based mercury sphygmomanometer, the MSM-based RS-611 is completely unobtrusive and the users do not need to attach any electrodes or devices on their body.…”
Section: Methodsmentioning
confidence: 99%
“…These repetitive partial or, in certain advanced cases complete obstructive episodes of the upper airway during periods of sleep, are characterized by cessation of breathing for at least 10 s per minute resulting in hypopneic scenarios leading to apnea[ 7 , 9 , 10 ]. Grading of OSA is based on the apnea-hypopnea index (AHI), which is defined as number of apnea and hypopnea episode per hour of sleep[ 17 ]. Mild OSA has an AHI of 5-14/h, moderate OSA 15-30/h AHI, and severe OSA has an AHI of > 30/h[ 18 , 19 ] (Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…This, in turn, leads to a high false positive result and a failure in the exclusion of low-risk patients [26]. Among newly proposed methods of OSA screening are photoplethysmography [27], ballistocardiography [28], piezoelectric sensors [29], accelerometers [30], audio signals [31], [32], and radar-based systems with non-contact sensing for sleep apnea and sleep body position, respectively: [33], [34]. Most methods which could be used for home detection of OSA were recently reviewed by Mendonca et al [11].…”
Section: Discussionmentioning
confidence: 99%